Perancangan Media Pembelajaran Berbasis Augmented Reality Menggunakan Aplikasi Assemblr Edu Pada Mata Pelajaran IPA Kelas VIII Di SMPN 1 Sungai Limau - Anggraini, Siti Rahma; Annas, Firdaus; Darmawati, Gusnita; Yuspita, Yulifda Elin (Universitas Lampung, 2024)
This research starts from the existence of problems at SMPN I Sungai Limau which still applies conventional learning and still dominantly uses printed books which causes students to have difficulty in understanding the material presented by the teacher because the learning process is less interesting and does not support science learning at school. Researchers conducted this study with the intention of producing an Augmented Reality-based learning media using the assemblr Edu application that is interesting and can help in the science learning process. The method that researchers apply in this problem is the Research and Development (R&D) development method. The development model used is the development model according to Hannafin and Peck which consists of three stages, namely Needs Analysis (Needs Assess), Design (Design), and Development and Implementation (Develop and Implement) where the three stages are interrelated with evaluation and revision. Researchers used three tests to assess the product: validity test conducted by five experts and resulted in a score of 0.90 with valid criteria; practicality test completed by three experts and resulted in a score of 0.99 with high criteria; and effectiveness test completed by 30 students and resulted in a score of 0.93 with high criteria.Kata kunci: Augmented Reality, IPA, Assemblr Edu